A Comparative Study to Assess Functional Outcomes and Proprioception in Remnant-Preserving versus Standard Anterior Cruciate Ligament Reconstruction - Sharat Balemane; Sushanth Sudhir Rao; Hishanil Rasheed; Imthiaz Ahammed (Journal of Orthopaedic Case Reports)
Introduction: Anterior cruciate ligament reconstruction (ACLR) is a commonly performed procedure for patients experiencing persistent symptomatic instability, aimed at achieving a functionally stable knee while minimizing the risk of secondary injuries and long-term complications. An anterior cruciate ligament (ACL) injury can result in damage and loss of proprioceptive receptors, leading to mechanical instability. As a result, current research is exploring innovative strategies to improve ACL healing, lower the failure rate, expedite recovery, and restore the biomechanics of the knee to pre-injury levels. Objectives: This study aimed to study the functional outcomes and post-operative proprioceptive function in patients who undergo remnant-preserving ACLR (RP-ACLR) compared to the standard ACLR (S-ACLR) technique. Materials and Methods: This prospective study was conducted among patients who presented with ACL injury, and who underwent either arthroscopic remnant RP-ACLR or arthroscopic S-ACLR. Patient’s functional outcome was measured by International Knee Documentation Committee (IKDC) subjective knee score, Lysholm knee score, Visual Analog Scale score, and proprioception by joint position error (JPE) in degrees was noted at presentation, at 15 days, 30 days, 3 and 6 months postoperatively. Results: A total of 30 cases of with ACL injury during the study period who underwent RP-ACLR and 30 cases of ACL injury who underwent S-ACLR. There were 83.3% males and 16.7% females in RP-ACLR group and 86.7% males and 13.3% females S-ACLR group with patients being maximally at the age group of 26–30 years (41.7%). The average time since injury of 4.04 months and average surgical time was 90 min. There was progressive improvement in functional outcome at 15 days, 30 days, 3 months, and 6 months (P = 0.01). At 6 months, the IKDC and Lysholm scores were 75.97 and 74.93 in the RP-ACLR group, 74.30 and 74.73 in S-ACLR group, respectively. There was a statistically significant enhancement in proprioception, measured by JPE in degrees between the groups as assessed at 15° flexion (P = 0.02), 45° flexion (P = 0.01), and 60° flexion (P = 0.01). Conclusion: Our results indicated no significant difference in functional outcomes between the two groups as assessed by the IKDC and Lysholm Knee scores, although both groups demonstrated significant improvements postoperatively. In conclusion, the significant differences in proprioceptive outcomes observed in the current study suggest that remnant preservation may enhance early sensory feedback post-ACLR.